Probabilitas dan Kinerja Pelayanan Transportasi Publik pada Bus Perkotaan dengan Metode CSI dan IPA Bus Transjatim Rute Bunder-Paciran - Latin, Nur Fauziyah; Ridwan, Ahmad; Mukhoyyaroh, Nur Indah (Universitas Batanghari Jambi, 2025)
Public transportation plays a crucial role in supporting community mobility while also reducing traffic congestion, pollution, and travel costs. The Trans Jatim Corridor IV bus service on the Bunder–Paciran route is an initiative by the East Java Provincial Government to enhance the quality of public transportation services. This study aims to assess user satisfaction with Trans Jatim’s services and analyze the probability of mode shift from previous modes of transportation to Trans Jatim. The methods employed include the Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and probability analysis using a Stated Preference approach and binary logistic regression. A total of 98 respondents were involved in data collection. The analysis results show a CSI index value of 0.85, indicating a